Pendidikan Ramah Anak: Upaya Reposisi Wacana Kemanusiaan dalam Potret Pendidikan Indonesia - Emna Laisa (Maharot : Journal of Islamic Education, 2021)
Education is a vehicle to actualize of the student’s potential. The potential is always nurtured to be fully utilized in their life. The focus here is not to actualize in the form of exploitation, exertion and violence but it is directed to create a metamorphosis from the ordinary into the extraordinary. Yet, the word “metamorphosis” misinterpreted to another meaning as creating hard educational models for the students. It seems as cognitive educational activities which shows student’s position as adult miniature. Here, the researcher will investigate the importance of discourse humanization as the concept of humanizing education. It’s inspire to create a concept of Sekolah Ramah Anak to be applied in educational institutions so that students feel that education is appreciates their souls.